2014
DOI: 10.1007/s13238-013-0001-4
|View full text |Cite
|
Sign up to set email alerts
|

Inflammasomes in cancer: a double-edged sword

Abstract: Chronic inflammatory responses have long been observed to be associated with various types of cancer and play decisive roles at different stages of cancer development. Inflammasomes, which are potent inducers of interleukin (IL)-1β and IL-18 during inflammation, are large protein complexes typically consisting of a Nod-like receptor (NLR), the adapter protein ASC, and Caspase-1. During malignant transformation or cancer therapy, the inflammasomes are postulated to become activated in response to danger signals… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
177
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 225 publications
(183 citation statements)
references
References 89 publications
6
177
0
Order By: Relevance
“…36 The inflammasome complex promotes inflammatory cell death through activation of cysteine protease caspase-1 and is purported to have tumor suppressive effects in some studies. 37 Our finding of upregulated GBP1, GBP4, and GBP5 in medullary carcinoma compared with all other colorectal carcinomas including microsatellite unstable colorectal carcinomas suggests a possible mechanistic link between the pro-inflammatory microenvironment and observed more favorable clinical outcomes in microsatellite unstable colorectal carcinomas.…”
Section: Discussionmentioning
confidence: 60%
“…36 The inflammasome complex promotes inflammatory cell death through activation of cysteine protease caspase-1 and is purported to have tumor suppressive effects in some studies. 37 Our finding of upregulated GBP1, GBP4, and GBP5 in medullary carcinoma compared with all other colorectal carcinomas including microsatellite unstable colorectal carcinomas suggests a possible mechanistic link between the pro-inflammatory microenvironment and observed more favorable clinical outcomes in microsatellite unstable colorectal carcinomas.…”
Section: Discussionmentioning
confidence: 60%
“…The authors also showed that ATP-release through Pannexin-1 channels of dying autophagic cells, P(2)X(7) purinergic receptor activation, and a functional K + -channel with potassium efflux are all necessary participants in activating inflammasome. Inflammasomes can be a double-edged sword in cancer [240]. …”
Section: (4) Cell-cell Communication and Anticancer Treatmentmentioning
confidence: 99%
“…Inflammasomes are closely related to chronic inflammation since they act as activators of IL-1β and IL-18 release by PBMC [22,23] . Moreover, activation of inflammasomes may stimulate cancer development [24] . The ability of PBMC to produce inflammatory cytokines plays a major role in the modulation of chronic inflammatory responses associated with carcinogenesis.…”
Section: Peripheral Blood Mononuclear Cells and Cytokine Productionmentioning
confidence: 99%